2020
DOI: 10.1111/gwao.12410
|View full text |Cite
|
Sign up to set email alerts
|

Are they ideological renegades? Fathers' experiences on taking parental leave and gender dynamics in Korea: A qualitative study

Abstract: Despite their fear of repercussions on career advancement and gender identity, Korean fathers taking parental leave have continually increased. Why do Korean fathers take parental leave in spite of the risk of being stigmatized as less masculine and less ideal workers? Are they willing to be ‘ideological renegades' to be new involved fathers? In‐depth interviews with fathers who took parental leave provide interesting answers. Overall, taking parental leave does not make fathers become ideological renegades si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Tribal stigma reflects membership in a group or category that is deemed inferior and discredited (Slutskaya et al, 2016). It tends to be genetically and culturally attached to individual traits, arising from one's race or ethnicity (Derous, Ryan, & Nguyen, 2012;Stewart & Shapiro, 2000), gender (Byun & Won, 2020;Martell & DeSmet, 2001), class (Brand & Thomas, 2014;Gray et al, 2018), and sexual orientation (Mize & Manago, 2018;Tilcsik, Anteby, & Knight, 2015). But tribal stigma can also impact occupations by association, wherein groups that are deemed "inferior" taint the entire occupation (Slay & Smith, 2011: 211).…”
Section: Sources Of Stigmamentioning
confidence: 99%
“…Tribal stigma reflects membership in a group or category that is deemed inferior and discredited (Slutskaya et al, 2016). It tends to be genetically and culturally attached to individual traits, arising from one's race or ethnicity (Derous, Ryan, & Nguyen, 2012;Stewart & Shapiro, 2000), gender (Byun & Won, 2020;Martell & DeSmet, 2001), class (Brand & Thomas, 2014;Gray et al, 2018), and sexual orientation (Mize & Manago, 2018;Tilcsik, Anteby, & Knight, 2015). But tribal stigma can also impact occupations by association, wherein groups that are deemed "inferior" taint the entire occupation (Slay & Smith, 2011: 211).…”
Section: Sources Of Stigmamentioning
confidence: 99%
“…The " fatherhood forfeit " of suspicion builds upon earlier work by Byun and Won (2020) who found that the initial reaction to Korean fathers taking up parental leave was largely "Umm … why should you? ", demonstrating the emergence of suspicion in a wider context.…”
Section: "It Wasn't Considered To Be Quite Normal"mentioning
confidence: 99%
“…In the US, there are no guaranteed paid paternal leave options (or maternal leave options), whereas 43 countries offer 14 or more weeks of paid paternal leave as of 2015 (Earle & Heymann, 2019). Too, even among countries with liberal paternal leave policies such as Korea (which offers up to 52 weeks of paid leave to fathers), company cultures do not always support men's taking advantage of such policies (Byun & Won, 2020).…”
Section: Proposed Modelmentioning
confidence: 99%